Analysis and design of a ZCT PWM DC-DC boost converter operating in BCM - Tiktas, Ertan; Gundogan, Abdulkerim; Bakan, Ahmet Faruk (SPRINGER, 2024)
A zero current transition (ZCT) pulse-width modulation (PWM) DC-DC boost converter operating in boundary conduction mode (BCM) is proposed in this paper. The auxiliary circuit of the proposed converter ensures the main switch to turn off with ZCT. Also, due to the operation of the proposed converter in BCM, naturally zero current switching (ZCS) is achieved for the turning on process of the main switch and the turning off process of the main diode. The proposed converter does not contain additional voltage and current stresses across the main components. The operation modes and theoretical analysis of the proposed ZCT PWM DC-DC boost converter operating in BCM are shown in detail. Detailed ZCT cell analysis and selection procedure of the resonant components which ensure the ZCT operation of the main switch are realized. The proposed converter is designed and tested, and experimental results are obtained in the laboratory. The total losses of the proposed converter are decreased by 53.77%, and its efficiency is increased by 3.2% compared to hard switching (HS) converter at 462 W nominal output power.
Keywords: Zero current switching (ZCS); Soft switching (SS); Zero current transition (ZCT); Boost converter; Boundary conduction mode (BCM); AUXILIARY CIRCUIT; FAMILY; CELL; Engineering